ZnO/SiO2 core/shell nanowires for capturing CpG rich single-stranded DNAs. Issue 3 (4th January 2021) - Musa, Marina; Yasui, Takao; Nagashima, Kazuki; Horiuchi, Masafumi; Zhu, Zetao; Liu, Quanli; Shimada, Taisuke; Arima, Akihide; Yanagida, Takeshi; Baba, Yoshinobu
Abstract : Modification of the surface of ZnO nanowires through atomic layer deposition (ALD) for the fabrication of a ZnO/SiO2 (core/shell) nanowire microfluidic device for capturing CpG-rich single-stranded DNAs (ssDNAs). Abstract : Atomic layer deposition (ALD) is capable of providing an ultrathin layer on high-aspect ratio structures with good conformality and tunable film properties. In this research, we modified the surface of ZnO nanowires through ALD for the fabrication of a ZnO/SiO2 (core/shell) nanowire microfluidic device which we utilized for the capture of CpG-rich single-stranded DNAs (ssDNA). Structural changes of the nanowires while varying the number of ALD cycles were evaluated by statistical analysis and their relationship with the capture efficiency was investigated. We hypothesized that finding the optimum number of ALD cycles would be crucial to ensure adequate coating for successful tuning to the desired surface properties, besides promoting a sufficient trapping region with optimal spacing size for capturing the ssDNAs as the biomolecules traverse through the dispersed nanowires. Using the optimal condition, we achieved high capture efficiency of ssDNAs (86.7%) which showed good potential to be further extended for the analysis of CpG sites in cancer-related genes. This finding is beneficial to the future design of core/shell nanowires for capturing ssDNAs in biomedical applications.